2016
DOI: 10.1093/icesjms/fsw136
|View full text |Cite
|
Sign up to set email alerts
|

Spatial prediction of demersal fish diversity in the Baltic Sea: comparison of machine learning and regression-based techniques

Abstract: Marine spatial planning (MSP) is considered a valuable tool in the ecosystem-based management of marine areas. Predictive modelling may be applied in the MSP framework to obtain spatially explicit information about biodiversity patterns. The growing number of statistical approaches used for this purpose implies the urgent need for comparisons between different predictive techniques. In this study, we evaluated the performance of selected machine learning and regression-based methods that were applied for model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…This is the reason why most model comparison studies with a binary response (e.g. Goetz et al (2015); Smoliński & Radtke (2016)) only use AUROC as a single error measure.…”
Section: Other Model Evaluation Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…This is the reason why most model comparison studies with a binary response (e.g. Goetz et al (2015); Smoliński & Radtke (2016)) only use AUROC as a single error measure.…”
Section: Other Model Evaluation Criteriamentioning
confidence: 99%
“…These have gained popularity due to their ability to handle high-dimensional and highly correlated data and the lack of explicit model assumptions. Some model comparison studies in the spatial modeling field suggest that machine learning models might be the better choice when the primary aim is accurate prediction (Hong et al, 2015;Smoliński & Radtke, 2016;Youssef et al, 2015). However, other studies found no major performance difference to parametric models Goetz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Then the comparisons between the four optimal models were made by assessing the performance measures on each fold. As the performances were measured using identically resampled datasets, statistical methods for paired comparisons can be used to detect pairwise differences in the performance among models [27,48]. Therefore, paired t-test was applied to verify if the differences in performance among the four optimal models with the significant level of 0.05.…”
Section: Model Comparisonmentioning
confidence: 99%
“…The most critical work in this study was to select the appropriate model based on the given datasets and to determine the optimized model parameters (called the hyperparameters) in the selected model to derive the most accurate output. We used the 10-fold cross-validation method to assess the accuracy of the different models [30]. Once models with good performance were selected, the grid-search approach was used to identify hyperparameters in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning is one of the reliable and cost-effective approaches that could reconstruct the inevitable gaps in the ocean color data and is a predictive model. In particular, the approach is more flexible than conventional parametric models because of its ability to handle non-linear relationships and complex interactions, which often occur in ecological data [28][29][30]. Jouini et al [9] attempted to recover significant gaps in satellite-derived chlorophyll concentration (CHL) data using Self Organizing Maps (SOM) classification (instance-based machine learning) in the western sector of the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%